The Utilization of Napier Grass Stems for Cd(II) Ions Removal from Aqueous Solution: Process Optimization Studies Using Response Surface Methodology - Tongpoothorn, Wimonrat; Somboon, Titikan; Sriuttha, Manop (Asian Health, Science and Technology Reports, 2020)
The aim of this research was to study the utilization of Napier grass stems (NGS) as an adsorbent for removing Cd(II) ions from aqueous solutions. The characteristics of adsorbency indicated that adsorption could occur via electrostatic interaction between metal ions and active functional groups on the rough surfaces of the adsorbent. The conditions of the adsorption process were optimized using the Response Surface Methodology (RSM). The three variables in this study were pH, initial concentration, and adsorbent dosage, which were decided by the Central Composite Design (CCD), while the response was considered by the adsorption capacity. The statistical analysis demonstrated that the proposed model was significant in response, precision, and reliability. The maximum adsorption capacity was 5.90 mg g-1 in a solution with a pH of 5.83, an initial concentration of 50.00 mg L-1, and with an adsorbent dosage of 0.10 g. It was found that the initial concentration of Cadmium solution and adsorbent dosage had a significant effect on the adsorption capacity. The equilibrium process of Cadmium adsorption was well-described by the Langmuir adsorption isotherm (R2=0.9918), and the adsorption kinetic corresponded to the pseudo-second order model (R2=0.9990). In addition, thermodynamic studies illustrated that the adsorption process was endothermic and non-spontaneous in nature. In summary, it was proved to be feasible that Napier grass stems could be used as an alternative and sustainable adsorbent for removing Cd(II) ions from aqueous solutions.